A General Ammonium Salt Assisted Synthesis Strategy for Cr3+‐Doped Hexafluorides with Highly Efficient Near Infrared Emissions. (24th June 2021) - He, Fanquan; Song, Enhai; Zhou, Yayun; Ming, Hong; Chen, Zitao; Wu, Jiachang; Shao, Peishan; Yang, Xianfeng; Xia, Zhiguo; Zhang, Qinyuan
Abstract: The discovery of highly efficient broadband near infrared (NIR) emission material is urgent and crucial for constructing NIR lighting sources and emerging applications. Herein, a series of NIR emission hexafluorides A2 BMF6 :Cr 3+ (A = Na, K, Rb, Cs; B = Li, Na, K, Cs; M = Al, Ga, Sc, In) peaking at ≈733–801 nm with a full width at half maximum (FWHM) of ≈98–115 nm are synthesized by a general ammonium salt assisted synthesis strategy. Benefiting from the pre‐ammoniation of the trivalent metal sources, the Cr 3+ can be more efficiently doped into the A2 BMF6 and simultaneously prevent the generation of the competitive phase. Particularly, Na3 ScF6 :Cr 3+ (λem = 774 nm, FWHM ≈ 108 nm) with optimal Cr 3+ ‐doping concentration of 35.96% shows a high internal quantum efficiency of 91.5% and an external quantum efficiency of ≈40.82%. A lighting emitting diode (LED) device with a NIR output power of ≈291.05 mW at 100 mA driven current and high photoelectric conversion efficiency of 20.94% is fabricated. The general synthesis strategy opens up new avenues for the exploration of Cr 3+ ‐doped high efficiency phosphors, and the as‐obtained record NIR output power demonstrates for NIR LED lighting sources applications. Abstract : A series of NIR emission hexafluorides are developed using a general ammonium salt assisted synthesis strategy. Particularly, Na3 ScF6 :Cr 3+ with optimal Cr 3+ ‐doping concentration of 35.96% shows a high internal quantum efficiency of 91.5% and external quantum efficiency of ≈40.82%. A NIR pc‐LED with a high photoelectric conversion efficiency of 20.94% is further fabricated, exhibiting good potential in the special lighting source application.